Implementasi Konsep Smart Environment pada Ruang Terbuka Hijau di Bukit Pelangi, Kota Sangatta - Lutfiah, Zauharatul; Mahnunah, Nimah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Bukit Pelangi Green Open Space has excellent potential to implement the concept of a smart city, especially in applying smart environmental dimensions with a focus on using technology to improve environmental quality, resource management efficiency, and public services. This study aims to determine the application of a smart environment in green open spaces in Bukit Pelangi, Sangatta City. This study uses a deductive approach with qualitative research methods. The data collection methodology includes literature studies, field observations, and stakeholder interviews on implementing a smart environment. This study uses a case study in Bukit Pelangi because the area is currently developing an integrated green open space with smart environmental technology. The study results show that Bukit Pelangi Park has tried to implement the concept of a smart environment. The application of this smart environment has met the suitability of the indicators of the availability and contribution of green open spaces, parks with WiFi facilities, the use of CCTV, and the existence of a waste bank. Indicators still less appropriate are the existence of an automatic watering system and an electricity network. Meanwhile, indicators that are not yet appropriate or face challenges include using solar panels and applying a zero-waste lifestyle.